Flood/Rob Handling Study with Polder System In Port of Tanjung Emas Area Semarang - Mahmudi Amir; Slamet Imam Wahyudi; Gata Dian Asfari (International Conference on Coastal and Delta Areas, 2017)
Tanjung Emas Port is located in Semarang City which is the Capital of Central Java Province. Port of Tanjung Emas has a very vital role in supporting the economy of Central Java and surrounding areas as the entrance and exit of goods both regionally and internationally. But the problem of inundation, especially in the port of Tanjung Emas Semarang is a routine problem that can not be resolved and become a scourge for the port service user in the port. The purpose of this research is to know the management of polder system to handle flood disaster in Port of Tanjung Emas Port Semarang both from operational aspect and its maintenance and also evaluate polder system performance as flood / rob disaster management system. This study is a case study, which is to investigate in depth about flood / rob handling system using polder system. The approach method used in this research is descriptive method. Respondents of this research are the parties in the port area that is the manager (PT Pelindo III), port and port hydrological experts both the workers and the harbor. Data collection was done by field observation, questionnaires and interview. Data were analyzed by descriptive analysis. Keywords: flood / rob handling, polder system, port ofTanjung Emas